Yesus Hamba TUHAN Yang Dipilih (Penggenapan Yesaya 42:1-4 dalam Matius 12:15b-21) - Warseto Freddy Sihombing; Parsaoran Tambunan; Arnol Martumpu Manurung (Jurnal Teologi Cultivation, 2021)
Abstract: There are many quotations or allusions in the Gospel of Matthew from the Old Testament (OT). He used to mention in his Gospels quotations from the OT which were undergoing such fulfillment in the events recorded before the quotation. This is also understood in the sense of allowing for a complete fulfillment at a later date. Another feature is that all parts of the scriptures as quoted by Matthew are fulfilled. The long fulfillment quote of Isa. 42:1-4 in Matthew chapter 12 meets both standards. In this article, we explore whether paying attention to Matthew’s redactional emphasis in the preceding narrative (12:14-16) can help explain the citation so that it conforms to Matthew’s normal way of using fulfilled OT quotations. There are new nuances and dynamics in the fulfillment of Isaiah’s prophecy in Jesus as the chosen Servant of LORD. Keywords: Servant of LORD, Matthew, Isaiah, fulfillment Abstrak: Ada banyak kutipan atau alusi dalam Injil Matius dari Perjanjian Lama (PL). Ia biasa dalam Injilnya menyebutkan kutipan dari PL yang sedang mengalami penggenapannya sedemikian rupa dalam peristiwa-peristiwa yang dicatat sebelum kutipan. Ini juga dimengerti dalam arti memungkinkan penggenapan yang lengkap di kemudian hari. Ciri lainnya adalah bahwa seluruh bagian kitab suci seperti yang dikutip oleh Matius digenapi. Kutipan pemenuhan yang panjang dari Yes. 42:1-4 dalam Matius pasal 12 memenuhi kedua standar tersebut. Dalam artikel ini, dieksplorasi apakah perhatian pada penekanan redaksional Matius dalam narasi yang mendahului (12:14-16) dapat membantu menjelaskan kutipan sehingga memenuhi cara normal Matius menggunakan kutipan PL yang digenapi. Terdapat nuansa dan dinamika baru dalam pengenapan nubuatan Yesaya di dalam Yesus sebagai Hamba TUHAN yang terpilih. Kata Kunci: Hamba TUHAN, Matius, Yesaya, penggenapan